Wetlands: An ecosystem service South Africa can afford to protect: a critical evaluation of the current legal regime and mechanisms to facilitate the use of payment for ecosystem services to the conservation of wetlands in South Africa - Herbst, Deidre Linda (Department of Public Law, 2016)
Wetlands cover a small portion of the world's surface a rea but they provide the most significant contribution to people for survival and sustainable development. In South Africa wetlands are considered the most threatened of all the country's ecosystems. South Africa's legal framework governing wetlands recognises the importance of natural infrastructure and its contribution to ecosystem services. Notwithstanding this recognition, the deteriorating status of South Africa's wetlands is evidence that the legal framework, dominated by a fragmented command and control approach, has not adequately addressed the risks or considered the integration of potentially innovative mechanisms to facilitate their protection and restoration. Payment for Ecosystem Services (PES) is a market based instrument which has proven to be a successful mechanism in several developed and developing countries for restoring the functioning of the natural environment and providing economic returns to those responsible for having done so. This dissertation proposes that PES will provide a viable and effective tool to complement the existing regulatory mechanisms in the South Africa legal framework to conserve wetlands. Albeit there are several challenges which would need to be overcome such as land tenure in rural areas. The successful rollout of PES can be achieved through improved co - operative governance, an increased focus and improved legal regime in the agriculture sector and the successful implementation of existing policies and strategies. It is critical that policy and regulations specific to a PES scheme are introduced to enable effective integration with the existing legal framework, facilitate participation, specifically of rural communities and efficient and effective administration.